PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. MURINI SAM SAM KELURAHAN PINGGIR KECAMATAN MANDAU KABUPATEN BENGKALIS - Revandy Caubertin Girsang; Machasin '; Restu ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study ams to determine the influences of leadership and variable compensation on employee produktivity at PT. Murini Sam Sam, Kelurahan Pinggir Kecamatan Mandau Kabupaten Bengkalis. As for the population in this study were employees in the production Departement PT. Murini Sam Sam, amounting to 136 and 58 employees in this study were sample dusing slovin. Analysis of the data used method is to use a simultaneous test, and test partial coefficient of Determination. The result showed that there were significant and positive effect of the variables of leadership and compensation, either simultaneously or partial, of the employee productivity PT. Murini Sam Sam 66,30%. Determined by factors of leadership and compensation, where the largest contribution is given by the variable leadership, and 33,70% determined by ther factor that affect of work productivityKeywords: Leadership, Compensation, Employee Productivity